Stimulasi kecerdasan bayi dengan pijat bayi di desa Muara Purba Nauli - Eliya Lia Wardayani (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
ABSTRACT Today the parents were often preoccupied with finding a tutor or a private teacher to teach their children at home to be a smart student. Which was not necessary if a mother begins to stimulate her child's intelligence from infancy. We know that the golden period in which a child's brain development was at age 1-2 what was commonly called